Estradiol and angiotensin II crosstalk in hydromineral balance: Role of the ERK1/2 and JNK signaling pathways. (13th May 2016) - Almeida-Pereira, G.; Coletti, R.; Mecawi, A.S.; Reis, L.C.; Elias, L.L.K.; Antunes-Rodrigues, J.
Highlights: The effect of estradiol on ANGII-induced fluid intake requires the ERK1/2 and JNK signaling. JNK signaling is involved in fluid intake induced by ANGII in OVX rats. Estradiol therapy decreased ANGII-induced oxytocin and vasopressin secretion. The vasopressin secretion induced by ANGII requires ERK1/2 signaling in OVX rats. Abstract: The angiotensin II (ANGII) receptor AT1 plays an important role in the control of hydromineral balance, mediating the dipsogenic and natriorexigenic effects and neuroendocrine responses of ANGII. While estradiol (E2) is known to modulate several actions of ANGII in the brain, the molecular and cellular mechanisms of the interaction between E2 and ANGII and its physiological role in the control of body fluids remain unclear. We investigated the influence of E2 (40 μg/kg) pretreatment and extracellular-signal-regulated kinase (ERK1/2) and c-Jun N-terminal kinase (JNK) cell signaling on the dipsogenic and natriorexigenic effects, as well as the neuroendocrine responses to angiotensinergic central stimulation in ovariectomized rats (OVX). We showed that the inhibitory effect of E2 on ANGII-induced water and sodium intake requires the ERK1/2 and JNK signaling pathways. On the other hand, E2 pretreatment prevents the ANGII-induced phosphorylation of ERK and JNK in the lamina terminalis. E2 therapy decreased oxytocin (OT) and vasopressin (AVP) secretion and decreased ERK1/2 phosphorylation in the supraoptic and paraventricular nuclei (SON and PVN, respectively). We found that the AVP secretion induced by ANGII required ERK1/2 signaling, but OT secretion did not involve ERK1/2 signaling. Taken together, these results demonstrate that E2 modulates ANGII-induced water and sodium intake and AVP secretion by affecting the ERK1/2 and JNK pathways in the lamina terminalis and ERK1/2 signaling in the hypothalamic nuclei (PVN and SON) in OVX rats.